Fractional thermal units as the base scale for estimation Of evapotranspiration for sorghum - SAMUI , R. P.; KALRA, POONAM (MAUSAM, 1992)
An attempt has been made to determine a base scale for evapotranspiration (ET) crop coefficient curves based on a fraction of thermal units concept, A crop coefficient curve for sorghum was developed using data obtained from 1982 through 1988 at Bellary, and then used to estimate ET for .1988-89 and .1989.90. The linear regression of estimated ET rates against measured ET rates was performed for both the years and were found significant at 1 % level.